NOVICE VERSUS EXPERIENCED TEACHERS: HOW THEY TRANSFORM THEIR VULNERABILITY INTO PROFESSIONAL IDENTITY IN AN INDONESIAN JUNIOR HIGH SCHOOL - Florida, Nancy Agatha; Mbato, Concilianus Laos (LPPM Undiksha, 2020)
The quality of education is influenced by many factors, one of which is the quality of the teachers. In the spirit of fostering a strong and resilient young generation, teachers in the capital city of Nusa Tenggara Timur (NTT), Kupang, attempted to break through their limitations in order to form their identity. This research investigated how novice and experienced teachers shifted their vulnerability into professional identity and to what extent this strategy impacted on their professional identity construction in a Junior High School in Kupang. This research presented a thematic analysis on their expectation and anxiety, their strategies and how these strategies helped them to build their identity. Results from data analysis clearly indicated that without critical reflections and actions, both novice and experienced teachers could undergo burnt out when dealing with their vulnerability.